3-12b=-9

Simple and best practice solution for 3-12b=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-12b=-9 equation:


Simplifying
3 + -12b = -9

Solving
3 + -12b = -9

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -12b = -9 + -3

Combine like terms: 3 + -3 = 0
0 + -12b = -9 + -3
-12b = -9 + -3

Combine like terms: -9 + -3 = -12
-12b = -12

Divide each side by '-12'.
b = 1

Simplifying
b = 1

See similar equations:

| 2.5+1.6k+3k+4.5=2.7k-0.9k | | 0.04x+0.20(80-x)=0.15(80) | | 4+2n=4 | | 3-3.7b=10.3b+0 | | 5+3b=17 | | 2x^3-5x^2+7x=0 | | y=-10.6-8 | | 2m-3=17 | | (x-5)(x+8)=8(x-2) | | 2.5+14.1k=3.6k | | 3-3.7b=10.3b | | 98x^3/y^5 | | 17x-20-7x=2(6x-4) | | 265-x=200 | | 1-3m=-17 | | 5q+4=8q-5 | | 4k^2+8k=0 | | -8d-5d+7d=71 | | 18+b=x | | 5x21/2 | | -r-4=-2 | | 2a-(5/a-1)=0 | | 99n+4=40 | | 5x-13=38 | | 3u-3=3u-6 | | 0=p+19 | | x-35=0 | | F(k+2)=3(2)+7 | | 21/26y=7 | | 23=23+x | | 0=4x^2+79x+376 | | y=1.3(-8)-8 |

Equations solver categories